2015
DOI: 10.1016/j.jand.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Food Away from Home Is Associated with Improved Child Relative Weight and Body Composition Outcomes and This Relation Is Mediated by Changes in Diet Quality

Abstract: Background Reducing consumption of food away from home (FAFH) is often targeted during pediatric obesity treatment given associations with weight status and gain. However, the effects of this dietary change on weight loss are unknown. Objective Evaluate associations between changes in dietary factors and child anthropometric outcomes after treatment. It is hypothesized that reduced consumption of FAFH will be associated with improved dietary intake and greater reductions in anthropometric outcomes (standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 30 publications
(29 reference statements)
1
38
0
1
Order By: Relevance
“…7 It has been shown that an intervention reducing the intake of food consumed away from home improved diet quality and body composition in overweight children. 32 Higher diet quality scores are independently associated with improved weight status in elementary schoolchildren, 33 and a recent meta-analysis showed that dietary patterns high in energy and fat and low in fiber are predictive of later obesity. 3 These studies suggest that it is reasonable to hypothesize that educational interventions that improve vegetable liking and intakeand lead to improved diet quality-may help students achieve a healthy BMI over time.…”
Section: Discussionmentioning
confidence: 99%
“…7 It has been shown that an intervention reducing the intake of food consumed away from home improved diet quality and body composition in overweight children. 32 Higher diet quality scores are independently associated with improved weight status in elementary schoolchildren, 33 and a recent meta-analysis showed that dietary patterns high in energy and fat and low in fiber are predictive of later obesity. 3 These studies suggest that it is reasonable to hypothesize that educational interventions that improve vegetable liking and intakeand lead to improved diet quality-may help students achieve a healthy BMI over time.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the mediation analysis in this study utilized nonexperimental data (i.e., mediators were not preselected and tested against a control), which may increase bias of the results . However, similar approaches are commonly used within the literature and serve to provide an initial test of causal models that can be confirmed with a follow‐up study designed specifically to address the challenges of mediation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study examined baseline FF as a predictor of FBT response and, consequently, how changes in FF may contribute to child weight and diet change following treatment. Finally, given the link between dietary and weight change our data have previously indicated , an exploratory mediation analysis assessed changes in food group consumption and diet quality as a mediator of the relation between children's FF change and weight change.…”
Section: Introductionmentioning
confidence: 99%
“…They also emphasise the need to raise parental awareness about the health risks associated with childhood overweight and obesity. Indeed, parents who are aware of these issues might be significantly more likely to get their children screened early, to improve their diet and to increase their physical activity than parents who are not aware .…”
Section: Discussionmentioning
confidence: 99%